2013
DOI: 10.1016/s0254-6272(13)60099-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation on effect of scalp electroacupuncture for mild cognitive impairment

Abstract: All the three therapies may improve the cognitive function of MCI patients. The therapeutic effects in the scalp electroacupuncture and syndrome differentiation groups were basically the same, but superior to nimodipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 9 publications
2
75
0
Order By: Relevance
“…All but five trials [43, 44, 46, 50, 51] required the appearance of poststimulating “de-qi” sensation, a critical factor for the effectiveness of acupuncture therapy. As to control groups, sham acupuncture alone was adopted in six trials [42, 43, 45, 46, 49, 50], and nine trials [40, 41, 44, 47, 48, 51, 52, 54, 55] used medication as controls; one trial [53] applied both sham acupuncture and medication in separate control groups. As to the implementation of sham acupuncture, nonacupuncture points were used in all of the relevant trials, except one [42] that chose the sham points in different innervation area from the acupuncture group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but five trials [43, 44, 46, 50, 51] required the appearance of poststimulating “de-qi” sensation, a critical factor for the effectiveness of acupuncture therapy. As to control groups, sham acupuncture alone was adopted in six trials [42, 43, 45, 46, 49, 50], and nine trials [40, 41, 44, 47, 48, 51, 52, 54, 55] used medication as controls; one trial [53] applied both sham acupuncture and medication in separate control groups. As to the implementation of sham acupuncture, nonacupuncture points were used in all of the relevant trials, except one [42] that chose the sham points in different innervation area from the acupuncture group.…”
Section: Resultsmentioning
confidence: 99%
“…NDI was applied as the primary outcome in seven trials, among which, four trials [43, 45, 46, 50] reported both NDSI and NDLQI, and three trials [41, 51, 53] only focused on NDLQI. SF-36 was measured by six trials [40–42, 45, 49, 54]. Eight trials [40, 42, 47–49, 52–54] evaluated symptom scores of the participants, but with different scoring standards.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis demonstrated that acupuncture improved picture recognition scores compared to the control group (MD 2.12, 95% CI 1.48 to 2.75; p<0.01). Finally, two trials 14 21 included CDT scores; however, one of these 14 did not report CDT results after treatment. The other 21 reported that patients treated with acupuncture did not significantly increase their CDT scores compared with those of the control group.…”
Section: Acupuncture Versus Conventional Therapymentioning
confidence: 99%
“…22 Two studies 14 21 did not report whether any adverse events or side effects had occurred in the experimental or control groups. DISCUSSION Although acupuncture has been used clinically in the management of AMCI in recent years, 14 no systematic review or meta-analysis has been performed to evaluate the effectiveness of acupuncture specifically for this condition. The present study analysed data from five RCTs involving 568 individuals to summarise and evaluate the available evidence on the efficacy and safety of acupuncture therapy for AMCI.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…As a novel combinational approach, electroacupuncture (EA) therapy, consisting of traditional acupuncture and modern electrotherapy technology, was frequently reported to alleviate cognitive decline in patients with stroke [2], Alzheimer disease (AD) [3, 4], or mild cognitive impairment (MCI) [57]. In addition, EA was suggested to prevent cognitive deficits in rats with cerebral ischemia [811].…”
Section: Introductionmentioning
confidence: 99%